Tislelizumab Plus Chemotherapy Sequential Neoadjuvant Therapy for Non-cCR Patients After Neoadjuvant Chemoradiotherapy in Locally Advanced Esophageal Squamous Cell Carcinoma (ETNT): An Exploratory Study - He, Wenwu; Wang, Chenghao; Wu, Lei; Wan, Gang; Li, Baisen; Han, Yongtao; Li, Haojun; Leng, Xuefeng; Du, Kunyi; Chen, Haijun; Wang, Qifeng; Peng, Lin (Frontiers in Immunology, 2022)
Background Esophageal squamous cell carcinoma (ESCC) remains a challenging malignant tumor with poor prognosis and limited treatment methods worldwide, and most patients are at a locally advanced stage at diagnosis. High recurrence and metastasis rates remain the main factors leading to the failure of the current standard treatment of neoadjuvant chemoradiotherapy plus surgery for resectable locally advanced ESCC. Improving the pathological complete response (pCR) rate may significantly benefit the survival of patients with resectable locally advanced ESCC after neoadjuvant therapy. Methods Tislelizumab plus sequential neoadjuvant chemotherapy was administered to non-clinical complete response (cCR) patients after neoadjuvant chemoradiotherapy for locally advanced ESCC. The patients then received surgery and adjuvant therapy according to the postoperative pathological results. Eighty patients with locally advanced ESCC were recruited for the study. The primary outcomes of the pCR rate and the incidence of adverse events will be analyzed completely within 24 months, and the secondary endpoints will include cCR rate, major pathological response rate, objective response rate, R0 resection rate, event-free survival, and overall survival. Discussion This study explored the safety and efficacy of tislelizumab plus chemotherapy sequential neoadjuvant therapy for non-cCR patients and provided a total neoadjuvant therapy model that can benefit patients with locally advanced ESCC. Clinical Trial Registration ClinicalTrials. gov NCT05189730. Registered: November 26, 2021, https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000BBD5&selectaction=Edit&uid=U0004UG3&ts=47&cx=e0cm59.